Quality of Life among Geriatric Population: A Community-based Study in the Rural Field Practice Areas of a Tertiary Care Hospital in Mangalore - V, Narayana; Kumar, Saurabh; Prabhu, Sudhir; Bhat, Sowmya; Dsouza, Oliver; Krishna, Nishanth; Shetty, Achal; D'souza, Moira; Thomas, Anissa; Suresh, Sucharitha (Journal of Pharmacy Practice and Community Medicine)
Background: Quality of life among elderly needs assessment as they are the growing population nowadays and also are more vulnerable to many morbid conditions. Objectives: The objective of this study is to assess different domains of quality of life and its relationship with socio-demographic factors. Methods: A Community based study was done among 153 persons aged 60 years and above from 13.06.2018 to 20.06.2018 in the rural field practice areas of Department of Community Medicine, Father Muller Medical College, Mangalore Karnataka. The World Health Organisation, Quality of life-BREF Questionnaire was used and analysis done using SPSS version 23.0. Results: The mean Quality of life score was maximum in social health domain (72.90 ±1.63) followed by environmental health domain (63.10 ±3.71) and physical health domain (61.60 ± 2.96). The lowest was in psychological health domain (57.90 ± 2.61). Better scores of physical health domain, Psychological health domain and social health domain was seen among the elderly who had easy contacts with other people in the community. Environmental health domain score was better among the elderly people belonging to the Christian religion. Conclusion: In our present study, social relationship domain had higher mean Quality of life score when compared to other domains; where as psychological domain was affected badly among the elderly population. Further counselling and research can be done to explore the factors affecting the psychological domain.
Keywords: Geriatric; Quality of life; Health status; India